The Use of Authentic Materials to Enhance Students’ Speaking Ability in Secondary EFL Classroom - Inezfarrah, Adinda Chika (RETAIN, 2021)
The purpose of this research is to determine whether the use of authentic material has an impact on enhancing EFL students' speaking ability. Conducted in MTs Unggulan in Surabaya, this research uses two classes of 8th grade, divided into two groups, experimental class and control class. This research uses authentic materials taken from YouTube, BBC official website, and several internet materials as a media to learn daily conversation. A quantitative method with a quasi-experimental design is used in this research. The data were collected by spoken tests, which are pre-test and post-test. The results presented a difference between the learning using authentic material and ones without authentic material. The asymptotic significance post-test value from Mann-Whitney is .00 < .05, with the median control group is 67.00, and the median from the experimental class is 75.00. This value shows authentic material is more effective to use as a medium to learn speaking for EFL students. Also, it is recommended to use as an appropriate alternative to enhance student’s speaking competence.